Delimiting Geopolitics: A formal approach to define the Geopolitical Subject - Gomes da Costa, De Leon Petta (Revista Brasileira de Estudos de Defesa, 2018)
Today the term "Geopolitics" is very used but only in few situations is correctly employed. Normally its mentions is without any geopolitical literature or even geographic/spatial information. For this reason, this research will explore the precision of the Geopolitical Subject.